Prevalence of Tinea capitis among school children in Galle Municipal area. - Kalukottege, R.M.P (My University, 2006)
The objectives of this study were to determine the prevalence of tinea capitis among prepubertal school children in Galle Municipal area to determine clinical types of tinea capitis and there causative agents, and also to identify the predisposing factors of tinea capitis among the study population. The data was collected using an interviewer administered questionnaire and by taking a brush sample of the scalp, following scalp examination. The brush samples were cultured for fungi according to standard laboratory methods. The data analysis was done by using EPI 2002 statistical analysis software (CDC ). Tinea capitis is apparently not a problem in the study area. The habits of frequent bathing and frequent application of hair oil may be unfavorable for tinea capitis infection as well as asymptomatic carriage.